Effect of filler load on the curing behavior and mechanical and thermal performance of wood flour filled thermoset composites - Nabinejad, O.; Debnath, Sujan; Rahman, Muhammad; Davies, Ian (Elsevier, 2017)
© 2017 Elsevier Ltd The mechanical and thermal performance of wood flour composites (WFCs) containing thermoset resin is known to be strongly dependent on the curing reaction. In the present work, WFCs were prepared based on either unsaturated polyester, vinylester or epoxy reinforced by oil palm shell (OPS) flour with a major focus being the preferential reaction of the curing initiator with the natural fiber cells instead of the thermoset resin. Increasing the loading of OPS was found to delay the curing reaction of all thermoset resins by decreasing the peak exothermic temperature and increasing the time to peak. Selecting a suitable surface treatment for the OPS was observed to play a significant effect on the rate of curing reaction. Thermal degradation (in an inert atmosphere) and linear shrinkage of the WFCs was found to decrease with an increase in filler load. In terms of the mechanical performance, the flexural modulus increased steadily with filler load whereas the tensile modulus reached its maximum value of 2.74 GPa (30% improvement) at a filler content of 23 wt% for the hot alkali treated OPS reinforced polyester composite. Increasing the filler load was found to decrease the tensile strength whilst the flexural strength experienced an optimal value of 70.6 MPa (28% improvement) for a filler load of 9 wt%. Furthermore, the OPS filler exhibited improved interfacial bonding with the polyester matrix when compared to vinylester and epoxy.